Open government data use in the Brazilian states and federal district public administrations - Kawashita, Ilka (2022)
The resulting dataset is available at: https://doi.org/10.34622/datarepositorium/UY7MFA as per the CC0—“Public Domain Dedication” License, accessed on 5 October 2021.